2019
DOI: 10.4236/jsea.2019.126014
|View full text |Cite
|
Sign up to set email alerts
|

A Survey on Software Cost Estimation Techniques

Abstract: The ability to accurately estimate the cost needed to complete a specific project has been a challenge over the past decades. For a successful software project, accurate prediction of the cost, time and effort is a very much essential task. This paper presents a systematic review of different models used for software cost estimation which includes algorithmic methods, non-algorithmic methods and learning-oriented methods. The models considered in this review include both the traditional and the recent approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
0
15
0
4
Order By: Relevance
“…This is why COCOMO is used extensively by project managers [16]. The COCOMO is one of the best known traditional models of programmatic estimate theories and it was proposed by the scientist Boehm in 1981 [17] and it is also called COCOMO1 or COCOMO81 and it is a group of three typical levels: basic, Intermediate, and detailed. They all have a relationship between system size measured in KLOC and effort developed in person per month [18].…”
Section: The Cocomo Modelmentioning
confidence: 99%
“…This is why COCOMO is used extensively by project managers [16]. The COCOMO is one of the best known traditional models of programmatic estimate theories and it was proposed by the scientist Boehm in 1981 [17] and it is also called COCOMO1 or COCOMO81 and it is a group of three typical levels: basic, Intermediate, and detailed. They all have a relationship between system size measured in KLOC and effort developed in person per month [18].…”
Section: The Cocomo Modelmentioning
confidence: 99%
“…Multiple studies reported that COCOMO-II supports a calibration process in an effective manner. In other words, it means that primary metrics used in COCOMO-II model are clearly defined, and the variables are presented in a more detailed manner [33]. Another noticeable advantage of using COCOMO-II is its ability to function more effectively due to dynamically adjusting according to the reported changes.…”
Section: Limitations Of Existing Cost Estimation Modelsmentioning
confidence: 99%
“…However, in the GSD context, the machine learning-based cost estimation models are only presented at a conceptual level [30]. Chirra et al [33] reported that when a model is created with different historical project datasets, there is a variation in the predicted accuracy. While using machine learning models in the GSD context, it is difficult to determine which technique will give more accurate results on which type of dataset.…”
Section: Limitations Of Existing Cost Estimation Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A busca pela otimização dos parâmetros do COCOMO Básico tem gerado muitos trabalhos nos últimos anos (Chirra et al 2019). Modelo Semi-Destacado 50-300 KLOC E = 3.0 * (KLOC) 1.20 Modelo Embarcado Acima de 300 KLOC E = 3.6 * (KLOC) 1.12 Quadro 4.…”
Section: Trabalhos Relacionadosunclassified